MASSAGE THERAPY IN THE RELIEF OF PAIN IN SPINE (Fiep Bulletin - online, 2012)
This study aims to identify the effects of massage therapy applied to a person with localized pains in the region of the spine. This study was conducted in the Hall Estétika Space, located in Curitiba-Pr, after prior approval of the establishment and patients who participated in the survey. Data collection was organized as follows: the patient with localized pains along the spine past the first session by a postural assessment and answered a questionnaire on quality of life and one of their main complaints. Since the first session to last a total of 10 sessions, applied twice a week, were answered the plug and plug the evolution of quality of life. The results showed improvements in pain along the spine, sleep, concentration, among others, and show that applied by the touch of massage therapy contribute to the improvement of pain, and indirectly the quality of life of the person being treated.
Keywords: Massage; Spine; Pains; Therapeutics.